Role of Extracellular Matrix in Acupoint Region in Acupuncture Effect - 张志英 党瑞山 金建华 黄轩 任丛莉 李亮 陈尔瑜 (Journal of acupuncture and tuina science, 2006)
Objective: To investigate the action mechanism of extracellular matrix in acupoint region in acupuncture signal transmission.Methods: Forty SD rats, half male and half female, were randomly allocated to the experiment group, basic pain threshold group, normal saline group and acupuncture group, with 10 rats in each group, the tail temperature at which rat flicks its tail in heat radiation tail flick test was taken as an observation index. In experiment group, the rats were given acupuncture treatment 30 min after injection of synthetic pentapeptide GRGDY (glycyl-arginyl-glycyl-aspartyl-tyrosine, Gly-Arg-Aly-Asp-Tyr) into “Housanli” area, basal pain threshold group, normal saline group which was given injection of 0.9% NaCl into “Housanli” area and acupuncture group which was given acupuncture at “Housanli” were used as controls.Results: As compared with acupuncture group, the temperature at which rat flicked its tail did not significantly changes following acupuncture 30 min after injection of GRGDY.Conclusion: GRGDY could not prevent the acupuncture effect, and the initial mechanism of acupuncture effect might have no relation to the structural site that extracellular matrix combines with integrin specially